2020
DOI: 10.1126/scitranslmed.aaz2415
|View full text |Cite
|
Sign up to set email alerts
|

CDK12 inhibition reduces abnormalities in cells from patients with myotonic dystrophy and in a mouse model

Abstract: Myotonic dystrophy type 1 (DM1) is an RNA-based disease with no current treatment. It is caused by a transcribed CTG repeat expansion within the 3′ untranslated region of the dystrophia myotonica protein kinase (DMPK) gene. Mutant repeat expansion transcripts remain in the nuclei of patients’ cells, forming distinct microscopically detectable foci that contribute substantially to the pathophysiology of the condition. Here, we report small-molecule inhibitors that remove nuclear foci and have beneficial effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 70 publications
0
17
1
Order By: Relevance
“…Interestingly, muscle sodium channel SCN4A transcripts were reduced in DM1 cells and antagomiR-218 treated myotubes compared with healthy controls, thus potentially contributing to DMPK downregulation (Figure S10D). CDK12 inhibitors are also capable of lowering DMPK transcript levels, but in HSA LR mice this was shown to reduce the transcription of the transgene itself, 55 which was not detected in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…Interestingly, muscle sodium channel SCN4A transcripts were reduced in DM1 cells and antagomiR-218 treated myotubes compared with healthy controls, thus potentially contributing to DMPK downregulation (Figure S10D). CDK12 inhibitors are also capable of lowering DMPK transcript levels, but in HSA LR mice this was shown to reduce the transcription of the transgene itself, 55 which was not detected in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…These kinases are important for transcriptional initiation and/or elongation. Cyclin-dependent kinase 12 (CDK12) is a transcriptional kinase comprised of 1490 amino acids, which has recently been shown to play a role in nuclear foci formation in DM1 [7]. It was first discovered in 2001 as a putative element of transcription process [8].…”
Section: The Role Of Cdk12 In the Production Of Dmpk Expansion Transc...mentioning
confidence: 99%
“…The main target of one subset of these kinase inhibitors was identified as CDK12, which provides a novel druggable molecular target for myotonic dystrophy. Ketley et al demonstrated the relationship between CDK12 and the production of mutant DMPK transcripts [7]. CDK12 inhibitors were found to eliminate the nuclear foci in DM cells as well as in the HSA LR mouse model, leading to potentially beneficial effects [7].…”
Section: Cdk12 As a Therapeutic Target For Myotonic Dystrophymentioning
confidence: 99%
“…By contrast, it has been described in DM5 mice that Celf1 phosphorylation is not affected by deficiency of PKCα or PKCβ and that these transgenic mice show similar disease progression when lacking both isoforms (Kim et al ., 2016). Data also suggest that CELF1 has PKC‐independent effects that are driven by other kinases (Ketley et al ., 2014), such as cyclin‐dependent kinase 12 (CDK12), which was recently identified as an interesting target in DM1 pathogenesis (Ketley et al ., 2020).…”
Section: Signalling Cascades That Contribute To Dm1 Muscle Atrophymentioning
confidence: 99%
“…In fact, as previously mentioned, it was found that STAU1 inhibits MEF2 thus proving that its overexpression in DM1 further impairs the differentiation of skeletal muscle cells (Ravel‐Chapuis et al ., 2014; Parks et al ., 2017). Also, it has recently been shown that CDK12, which is required for the maintenance of genomic integrity during embryonic development (Juan et al ., 2016), is elevated in DM1 cell lines and patient biopsies (Ketley et al ., 2020).…”
Section: Cellular Processes Implicated In Dm1 Muscle Atrophymentioning
confidence: 99%